Neue Tendenzen in den Sozialstrukturen Lateinamerikas - Boris, Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
The first part describes changes at the bottom of Latin American societies, especially the reduction of the poverty rate, the moderate decline of social inequality as well as the decrease of informal modes of labour. These changes are examined against the background of a strong economic expansion during the last decade. In the second part the recent growth of middle class-sectors in various countries is analyzed. In the last chapter the focus is on the ruling classes, who have come up with new forms of active internationalization. A brief discussion of the political implications of these tendencies concludes the article.